Demographic Profile, Knowledge, Attitude, and Practices of Blood Donors in a Low-Middle Income Country - Angelie Abegail Q. Naranja; Myra Dela Peña Oruga; Sheila R. Bonito (Faculty of Nursing Universitas Padjadjaran, 2021)
Background: Demographic profile, knowledge, attitude and practices (KAP) of blood donors in a low-middle income setting was investigated in this study. The study determined the demographic profile of blood donors in terms of sex, age, ethnicity and level of education and measured the level of knowledge, attitude and practices in terms of blood donation.Purpose: The relationship of the donor profiles in terms of level of knowledge, attitude and practices was also determined. Methods: It utilized a cross-sectional study design which was conducted from February-October 2020. A self-administered questionnaire was distributed to the volunteers of blood donors of a non-institution-based blood bank establishment in Baguio City. Descriptive statistics and Chi-square were used to analyze the data. Ethical clearance was obtained and was approved. Results: The results revealed that the majority of the respondents were female (59.2%) with age ranged from 18–30 years old (75.3%) and in collegiate level (83.2%). Majority of the respondents’ ethnicities were Tagalog (25.9%). Study revealed that respondents have a high level of knowledge in relation to blood donation, the attitude of the respondents revealed that blood donor had strong agreement to positive statements and disagreement to negative statements. Most of the respondents donated in the past, 62.3% are lapsed donors, 18% were first time donors and the majority had an intention to donate in the future. Conclusion: In terms of relationship of Demographic Profile to KAP, only Practices revealed a significant relationship to sex, age, ethnicity and level of education with P value ranging from 0.05- <0.0001.